Retrospective review of Synacthen testing in infants. Issue 10 (12th January 2018) - Tan, Timothy Shao Ern; Manfredonia, Claire; Kumar, Rakesh; Jones, Julie; O'Shea, Elaine; Padidela, Raja; Skae, Mars; Ehtisham, Sarah; Ivison, Fiona; Tetlow, Lesley; Clayton, Peter E; Banerjee, Indraneel; et al.
Abstract : Background: A subnormal cortisol response (30 min level (C 30min )<550 nmol/L) to synthetic adrenocorticotrophic hormone/Synacthen test (SDST) in all infants does not necessarily indicate underlying or persistent hypothalamic–pituitary–adrenal axis pathology. Methods: We retrospectively evaluated the diagnoses and outcomes in 68 infants who had a SDST at age <6 months from 2011 to 2014. Results: 29 (43%) infants had a subnormal SDST. Causative pathology was identified in 9/29 (31%). In 20/29 (69%) with no identified pathology, repeat SDST was normal in 18/20 (90%) at median age 0.6 (range 0.1–3.2) years but persistently subnormal in 2. Those with a transient abnormality were more likely to be small for gestational age (P=0.03) and had higher initial SDST C 30min (390 nmol/L vs 181 nmol/L, P=0.01) than those with pathology. Conclusion: Specific aetiology can be identified in a third of infants with a subnormal SDST. When the aetiology remains elusive, adrenal function should be reassessed as the problem can be transient.